Identifying factors influencing program selection in health sciences by underrepresented minority students—a scoping review - Mohammed, Sami Al Sufi; Roduta Roberts, Mary (Frontiers in Education, 2024)
There is a critical need to diversify health professionals to better serve the growing minority population in North America. Unfortunately, minority groups remain underrepresented in health professions. Despite recruitment efforts by government and academic institutions, fewer underrepresented minority (URM) students choose careers in healthcare. Identifying the key factors influencing URM students’ decisions to pursue health sciences programs could enhance diversity in these programs through targeted admissions strategies, ultimately leading to a more diverse future healthcare workforce. This scoping review was conducted in accordance with the Joanna Briggs Institute methodology for scoping reviews. Five electronic databases and gray literature were searched to identify North American papers published between 1942 and 2022. Identified studies focused on URM students’ perceptions of facilitators and barriers to matriculate into a health science degree. Twenty-one articles were analyzed. Following content analysis, the facilitators and barriers identified comprised personal, socio-cultural, institutional, and financial. The most frequent facilitators reported were scholarships, family support, and the presence of role models. Common barriers included high tuition fees, pre-admission criteria, lack of awareness about the health profession, availability of financial aid, and the admission process. The findings of this review will facilitate the development and implementation of customized, comprehensive strategies to recruit more URM students to health science programs in the future, thereby improving efforts toward creating a diverse healthcare workforce.